Stage 1 Registered Report: The relationship between handedness and language ability in children - Pritchard, VE; Malone, SA; Burgoyne, K; Heron-Delaney, M; Bishop, DVM; Hulme, C (F1000Research, 2019)
Weak or inconsistent hand preference may be a risk factor for developmental language delay. This study will test the extent to which variations in language skills are associated with the strength of hand preference. Data are drawn from a large sample (n = 569) of 6- to 7-year-old children unselected for ability, assessed at two time points, 6 months apart. Hand preference is assessed using the Quantitative Hand Preference task (QHP) and five uni-manual motor tasks. Language skills (expressive and receptive vocabulary, receptive grammar, and morphological awareness) are assessed with standardized measures. If weak cerebral lateralisation (as assessed by the QHP task) is a risk factor for language difficulties, it should be possible to detect such effects in the large representative sample of children examined here.